Lower urinary dysfunction as a long-term effect of childhood vincristine treatment, with potential influences by sex and dose - Nao Iguchi; Ali Teimouri; Duncan T. Wilcox; Anna P. Malykhina; Nicholas G. Cost (Scientific Reports)
Abstract Vincristine (VCR) is one of the most widely used chemotherapy agents in treating pediatric cancer. Nonetheless, it is known to cause dose-dependent neurotoxicity which can impact virtually every organ system. Despite its widespread use, the precise impact of VCR on the lower urinary tract (LUT) remains inadequately elucidated. Our initial clinical and translational investigations suggest a sex-specific influence of childhood VCR exposure on LUT function. Thus, the current study aimed to investigate the late effects of systemic VCR exposure on LUT physiology and the underlying mechanisms, focusing on dosage and male-sex, employing juvenile CD-1 mice as a model. Male mice subjected to VCR exhibited augmented functional bladder capacity accompanied by frequent non-void contractions during awake cystometry, alongside mast cell accumulation within the bladder, compared to the saline-treated control group. Noteworthy functional changes were observed in bladder strips from the VCR group, including decreased nerve-mediated contraction, heightened contractile responses to cholinergic and purinergic agonists, enhanced responsiveness to histamine—primarily via histamine receptor 1 (Hrh1)—and an augmented relaxation effect with compound 48/80 (a mast cell degranulator), relative to the control group. Significant changes in gene expression levels associated with neuroinflammation and nociception were observed in both the bladder and lumbosacral dorsal root ganglia (Ls-DRG) of the VCR group. These findings suggest that VCR exposure during childhood, particularly in males, triggers neuroimmune responses in the bladder and Ls-DRG, amplifying responsiveness to neurotransmitters in the bladder, thereby contributing to LUT dysfunction characterized by a mixed bladder phenotype as a late effect during survivorship.